2015
DOI: 10.4193/rhin14.078
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of cytokine release from epithelial cell cultures of the upper airway

Abstract: Epithelial cells derived from AR and CRSwNPs showed up-regulation of secretion of several cytokines/chemokines both in the steady state and after IL-17A stimulation, which may contribute to the inflammatory responses of AR and CRSwNPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…However, the neutrophilic type of infiltration predominates in some nasal polyp patients, especially in Asian and eastern populations. 2 The pathogenesis of PAR is well explained by antigen-specific T helper 2 (Th2) cells and their cytokines, especially interleukin-5 (IL-5) and IL-13, and by the release of enzymes in the late phase of allergic inflammation. 1,3 These enzymes, especially the eosinophil cationic protein (ECP), can damage the nasal epithelial cells and cause localized edema, resulting in the hyperreactivity of the upper airway and remodeling of the nasal mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…However, the neutrophilic type of infiltration predominates in some nasal polyp patients, especially in Asian and eastern populations. 2 The pathogenesis of PAR is well explained by antigen-specific T helper 2 (Th2) cells and their cytokines, especially interleukin-5 (IL-5) and IL-13, and by the release of enzymes in the late phase of allergic inflammation. 1,3 These enzymes, especially the eosinophil cationic protein (ECP), can damage the nasal epithelial cells and cause localized edema, resulting in the hyperreactivity of the upper airway and remodeling of the nasal mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, increased expression of IL-6 messenger RNA in nasal mucosa biopsies of patients suffering from persistent AR has been reported [45], pollen exposure to patients with AR significantly increased IL-6 in nasal secretions [5], and nasal secretions were increased in allergic patients after intranasal administration of IL-6 [39]. In addition, it has been reported that primary cultures of human nasal epithelial cells from patients with AR showed significant upregulation in the release of IL-6 [46, 47].…”
Section: Discussionmentioning
confidence: 99%
“…epithelial and endothelial cells) have been reported to produce neutrophil chemokines in response to inflammatory stimuli or foreign invaders [26]. In CRS, nasal epithelial cells are an important source of neutrophil chemokines as they have been documented to secrete CXCL8 in response to diesel exhaust particle, bacteria, or inflammatory stimuli [27-30]. In addition, CXCL1, CXCL2, and CXCL8 can be produced by fibroblasts [31,32], neutrophils [6] and mast cells [33] in nasal tissues under the stimulation with different triggers.…”
Section: Local Recruitment Of Neutrophils In Crsmentioning
confidence: 99%